(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
Although, the PMMA have good advantages made it appropriate to denture base applications. But its low impact and fracture strength represent the main drawbacks of it.so many studies had been done in order to overcome these problems. In this study Pistachio Shell powder was added in different weight fractions of about (3, 6, 9 and 12 wt. %) and different average particle sizes of about (53µm, 106µm, 150µm and212µm) to (heat-cure) PMMA that is popularly utilize in denture base applications and study the Fourier transform infrared spectroscopy (FTIR) and Differential Scanning Calorimeter (DSC) behavior of this bio composite. The results were as the following: the FTIR results demonstrated that there are no new peaks appeared after the reinforcing by Pistachio Shell powder. Also there was no shifting in any of these peaks. While the DSC test showed that the glass transition temperature (Tg) increased as the particle size of Pistachio Shell powder increased. The highest value of Tg (126.9?) was obtained for composite specimen reinforced with 12% of Pistachio Shell powder with average particle size of about (212µm).